Development and Validation of Kompetitive Allele-Specific PCR Assays for Erucic Acid Content in Indian Mustard [Brassica juncea (L.) Czern and Coss.] - Gill, Karanjot Singh; Kaur, Gurpreet; Kaur, Gurdeep; Kaur, Jasmeet; Kaur Sra, Simarjeet; Kaur, Kawalpreet; Gurpreet, Kaur; Sharma, Meha; Bansal, Mitaly; Chhuneja, Parveen; Banga, Surinder S. (Frontiers in Plant Science, 2021)
Brassica juncea L. is the most widely cultivated oilseed crop in Indian subcontinent. Its seeds contain oil with very high concentration of erucic acid (≈ 50%). Of late there is increasing emphasis on the development of low erucic acid varieties because of reported association of the consumption of high erucic acid oil with cardiac lipidosis. Erucic acid is synthesized from oleic acid by an elongation process involving two cycles of four sequential steps. Of which, the first step is catalyzed by β-ketoacyl-CoA synthase (KCS) encoded by FAE 1 gene. Mutations in the coding region of FAE1 lead to the loss β-ketoacyl-CoA synthase (KCS) activity and consequently a drastic reduction of erucic acid in the seeds. Molecular markers have been developed on the basis of variation available in the coding or promoter region(s) of FAE 1. However, majority of these markers are not breeder friendly and are rarely used in the breeding programmes. Present studies were planned to develop robust KASPar assays with high throughput and economics of scale. We first cloned and sequenced FAE1.1 and FAE1.2 from high and low erucic acid (<2%) genotypes of B. juncea (AABB) and its progenitor species, B. rapa (AA) and B. nigra (BB). Sequence comparisons of FAE1.1 and FAE1.2 genes for low and high erucic acid genotypes revealed SNPs at 8 and 3 positions. Of these 3 SNPs for FAE 1.1 and 1 SNPs for FAE 1.2 produced missense mutations, leading to amino acids modifications and inactivation of KCS enzyme. We used SNPs at positions 735 and 1476 for genes FAE1.1 and FAE1.2 respectively to develop KASPar assays. These markers were validated on a collection of diverse genotypes and a segregating backcross progeny. KASPar assays developed in the present study will be useful for marker assisted breeding as these can track recessive alleles in their heterozygous state with high reproducibility.